Going beyond won-loss record to identify successful coaches: Development and preliminary validation of the coaching success questionnaire-2 - Gillham, A.; Burton, D.; Gillham, E. (International Journal of Sports Science and Coaching, 2013)
The Coaching Success Questionnaire-2 (CSQ-2) was developed to provide a global assessment of coaches' ability to develop critical athlete outcomes (e.g., self-confidence). Study 1 examined the responses of 212 collegiate athletes on the 106-item CSQ-2A, and exploratory factor analysis (EFA) results provided empirical guidance for modification and refinement of the instrument. Study 2 utilized EFA and covariance modeling to examine the responses of 352 participants on the 76-item CSQ-2B, resulting in the final 40-item, 10-factor model. Study 3 confirmed the model with a sample of 396 athletes demonstrating strong factorial validity (i.e., RMSEA =.07; SRMR =.05; NNFI =.98; CFI =.99). Construct validity of the CSQ-2 was also examined using bivariate correlations and multivariate analysis of variance across psychosocial correlate variables (i.e., athlete self-confidence, enjoyment/boredom, motivational climate and athlete burnout). Results provided preliminary support for the construct validity of the CSQ-2 and discussion focused on possible uses of this new measure of coaching success as both a research and coach development tool.